Ciliberto e Vacca: Per l’autonomia fifilosofifica del marxismo - Panichi, Alessio (International Gramsci Journal, 2023)
This is the Abstract of the double review in Italian by Alessio Panichi of the volumes In cammino con Gramsci by Giuseppe Vacca (Roma, Viella, 2020) and La fabbrica dei Quaderni. Studi su Gramsci by Michele Ciliberto (Pisa, Edizioni della Normale, 2020). The former analyses Gramsci’s elaboration of the philosophy of praxis and the latter looks how Gramsci’s reading of the national history and cultural tradition of Italy informed the concepts developed in the Prison Notebooks.